Baruch's Jerusalem: The Conception of Jerusalem in 1 Baruch 4:5-5:9 - Henderson, Ruth (Journal of Biblical literature, 2016)
The final section of the book of 1 Baruch (4:5-5:9), which contains a song of exhortation and encouragement to Israel, is unified by a remarkably variegated emphasis on the city of Jerusalem. In this section, the city is dramatically personified as an aggrieved parent (4:5-9a), a lamenting, widowed mother (4:4:9b-16), an exhortatory prophet (4:17-29), and a glorious city of the future (4:30-5:9). While the personification of Jerusalem as a widowed, bereaved mother and glorious city of the last days is well known from scriptural texts such as Lam 1 and Isa 40-66, the conception of the city as an exhortatory prophet, not found in biblical sources, shows considerable development. Jerusalem is given a prophetic voice and role as one who intercedes for her exiled children, exhorts them to endurance and repentance and encourages them with the hope of restoration and return. The significance of this presentation of Jerusalem needs further investigation. The aim of this study is to explore this development in the conception of Jerusalem with particular emphasis on 1 Bar 4:17-29, against the background of its Second Temple provenance.